The Effect of Industrial Harmony Towards Employee Performance and Organizational Citizen Behaviour at Manufacturing Industry in Johor Bahru - ismail, fadillah (Research in Management of Technology and Business, 2022)
Industrial harmony serves as an important element in helping to increase competitiveness, increase productivity and achieve good work results for an organizational. The escalation of the COVID-19 pandemic has caused several problems such as low performance of employees in carrying out tasks and poor organizational citizen behaviour exhibited by employees. Therefore, the objectives of this study were to measure the level of industrial harmony and examine the effect of industrial harmony on employee performance and organizational citizen behaviour among employees at manufacturing industry in Johor Bahru. Quantitative methods have used to collect data through an online questionnaire with collect 132 sample size from 200 employees of an electrical and electronics company that represents the manufacturing industry. The data were analyzed by descriptive analysis and inferential statistic. Overall, the finding of this study has showed that the industrial harmony was at a good level and there was positive relationship between the industrial harmony and employee performance (r=0.477) and organizational citizen behaviour (r=0.289). This study also has proved that industrial harmony has significant effect towards employee performance (